United States parents` perfectionism, parenting styles and perceptions of specialization in youth sport - Wright, E.; Chase, M. A.; Horn, T. S.; Vealey, R. S. (Psychology of Sport and Exercise, 2019)
This study examined parents` perceptions of sport specialization within the sampling years of the Developmental Model of Sport Participation (DMSP) (Côté, 1999). Specifically, this study explored if and how parents` perceptions of sport specialization vary as a function of their own levels of perfectionism and self-reported parenting style. Design: Cross-sectional survey. Method: Self-report questionnaires were administered to 203 parents of youth sport athletes (ages 6-12) from a range of sports. These questionnaires assessed parents' perceptions of sport specialization as well as their own levels of perfectionism and parenting style. Results: Cluster analytic procedures resulted in the identification of four groups of parents who varied from each other in parenting style (permissive, authoritarian, authoritative) and perfectionism (self oriented, socially prescribed, other oriented). MANOVA procedures used to compare the four cluster groups on their perceptions of sport specialization revealed that parents who were in the high permissive and high socially prescribed perfectionism cluster as well as the high authoritarian and high overall perfectionism cluster reported greater support of sport specialization when compared to participants in the high authoritative, moderate self-oriented perfectionism cluster. Conclusion: Overall, study findings provided support for the idea that parents` perceptions of sport specialization are influenced by their parenting style and personal levels and types of perfectionism. Highlights - Parent clusters differ in profiles on perfectionism and parenting style measures - Parent perfectionism and parenting styles are related to perceptions of sport specialization - Different parent clusters vary in regard to their perceptions of sport specialization